PENGARUH PEMBERIAN MOTIVASI TERHADAP SEMANGAT KERJA KARYAWAN BISNIS PERBANKAN (STUDI PENERAPAN NEED ACHIVEMENT PADA BANK BNI CABANG RENGAT) - Lesmarni "; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was to determine the Effect of Motivation on Employee Morale Business Banking (Studies Achievement In Need Implementation of Bank BNI Branch Rengat). This research is located PT. Bank Negara Indonesia (Persero) Tbk Branch Rengat. Which is located on Regent Street 17 B Sincere Rengat. The research population is all employees at PT. Bank Negara Indonesia (Persero) Tbk Branch Rengat which amounts to 32 people. Analysis of the data in this study using SPSS. The sampling technique used is the method of census data and testing techniques used in this study include validity, reliability, simple linear regression and t-test to test and prove the research hypothesis.The analysis showed that the Effect of Motivation on Employee Morale Business Banking (Studies Achievement In Need Implementation of Bank BNI Rengat). Based on the results obtained by the value of r (correlation coefficient) of 0.691% means that 69.1% application need achievement motivation variable significant effect on the morale of Bank BNI Rengat. Results of hypothesis testing found that t-count larger than t-table which means Ha accepted.Keywords: Motivation, Need Achievement, and spirit at work